“CANGKRU’AN” DAN HARMONISASI KEHIDUPAN UMAT BERAGAMA - Syamsun Niam Syamsun Niam; Anin Nurhayati (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2021)
The above theme was raised because of considerations regarding the emergence of the phenomenon of hardening religious understanding by some people/groups which has implications for the continuity of the harmonious life of the nation’s citizens to be disturbed. Although the phenomenon of hardening religious understanding is only carried out by some people/small groups in Indonesia, it cannot be ignored considering the impact it has. In that context, it is important to conduct this research, with the aim that the hardening of religious understanding does not run wild and have an impact on the emergence of disharmony. The approach used in this research is natural and phenomenological. Methods of data collection use interviews, observation participation, and documentation. Finally, the conclusions obtained are: Pinang Asri residents find their own way of interpreting inclusivism through “cangkru’an”, although in practice there are obstacles, and cangkru’an Pinang Asri residents in order to stem the exclusiveness of religion is through various forms of activities.